Socialist architecture in Mao's model village: a case study of Qinyong Village in Ningbo - Xie, Jing; Deng, Wu (Taylor & Francis, 2017)
In the context of current drives for the renewal and conservation of rural Chinese villages, socialist villages developed under Mao Zedong’s tenure as Chairman of the Chinese Communist Party (1949-1976) seem have been marginalized. This research selects one of Mao’s model villages, Qinyong village in Ningbo, Zhejiang Province, as a case study. Through historical and on-site research, this article articulates and analyses the transformation of the village landscape from the early socialist period to the latest renovation in 2014. Focusing in particular on the transformation of the village’s housing from the 1970s to the 1990s, the article tries to identify historical conditions of social, political and economic organization embedded in their physical forms. By juxtaposing the recent planning and renovation of the village with its past, the discussion of the village’s architectural heritage is intended to cast some light on key aspects of village preservation and revitalization in rural China.